Abdominoplasty in gastric bypass patients: anthropometric profile, comorbidities, and complications - Simone Corrêa Rosa; Jefferson Lessa Soares de Macedo; Flávio Gondim Freitas; João Luiz Darques Ferreira; Lucas Ribeiro Canedo; Luiz Augusto Casulari (Revista Brasileira de Cirurgia Plástica, 2018)
Introduction: Patients who undergo vertical-banded gastroplasty- Roux-en-Y gastric bypass (VBG-RYGB) have significant weight loss, and abdominoplasty (AP) is an effective corrective surgery for removing excess skin. Methods: A prospective study conducted from January 2011 to December 2016 in a public hospital evaluated patients who underwent AP after VBG-RYGB. The analyzed variables were body mass index (BMI) before VBG-RYGB, BMI before AP, weight loss, weight of the excised abdominal flap, comorbidities, and complications. Results: For this study, 107 patients who underwent AP were included. The patients' mean age was 41 years; BMI before AP, 27.6 ± 3.7 kg/m2; and mean weight loss, 47.7 ± 17.3 kg. The maximum BMI before bariatric surgery was 45.5 ± 7.5 kg/m2, and the difference between the maximum BMI before VBG-RYGB and before corrective surgery was 18.6 ± 9.3 kg/m2. The comorbidities observed before VBG-RYGB were arterial hypertension (11.1%), arthropathy (4.6%), diabetes mellitus (5.6%), and metabolic syndrome (5.6%). Fourteen patients (13.1%) underwent herniorrhaphy during AP. The overall complication rate was 31.5%. Weight before VBGRYGB, BMI before VBG-RYGB, mean weight loss, comorbidities, abdominal flap weight, and BMI of >20 kg/m2 were significantly associated with postoperative complications. Conclusions: VBGRYGB was an effective approach to reduce comorbidities in obese patients. Comorbidities, weight before VBG-RYGB, mean weight loss, amount of tissue removed from the abdomen, and BMI of >20 kg/m2 significantly increased the complication rate in the gastric bypass patients who underwent AP. Furthermore, AP is fundamental for the comprehensive care of obese patients and has optimized the results achieved with VBG-RYGB.